DOWN TO EARTH WITH NIETZSCHE: The ethical effects of attitudes toward time and body - Sybylla, Roe (Ethical theory and moral practice, 2004)
This paper is about the effects on people's lives of their attitudes towards time and their own embodiment. People commonly see time as biform; there is the time of bodily life and the eternal time which transcends mortal life. This division is deeply implicated in the dualistic values that pervade western thought. So, when Nietzsche substitutes a monist notion of time, he profoundly unsettles our cherished values (which, of course, are gendered). Nietzsche's major thrust, I argue, is to elucidate and advocate the more appropriate values that emerge when human existence is understood as entirely earthborn., I use two contrasting literary characters to show concretely how people's lives and relationships are affected negatively or positively according to the temporal perspectives they adopt (and thus the significance they give to their corporeality). I explain how acceptance of human finitude enables a fruitful and rewarding life, while its refusal is life-diminishing. This also makes conceivable a realm beyond gender.